IMPLEMENTATION OF GREEN HOTEL IN SUPPORTING SUSTAINABLE TOURISM AT THE 1O1 BOGOR SURYAKANCANA HOTEL - Nataela Ratna Pandi; Dewanta Facrureza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The growth of the accommodation industry is expected to maximize the benefits achieved through more environmentally responsible accommodation. Waste and emissions generated in the surrounding environment can lead to global warming. This research aims to examine the implementation of green hotels in supporting sustainable tourism at THE 1O1 Bogor Suryakancana Hotel with reference to the ASEAN Green Hotel Standard (2018). The type of research is a combination method with sequential exploratory mixed methods, combining qualitative and quantitative to review and analyze data with observation, interviews, documentation and questionnaire distribution to 20 respondents. The sampling technique in this study used purposive sampling technique, namely head of department and supervisor. The results showed that THE 1O1 Bogor Suryakancana Hotel has implemented green hotels in supporting sustainable development goals, especially SDG 6, SDG 7, SDG 12, and SDG 13. The implementation of green hotels at THE 1O1 Bogor Suryakancana Hotel is based on the ASEAN Green Hotel Standard (2018) with 11 variables. The percentage value of the questionnaire results shows a value range of 61%-80% with the criteria for the level of suitability of implementation accordingly and a value of 81%-100% with the criteria for the level of suitability of implementation very suitable. With the results of the research analysis, THE 1O1 Bogor Suryakancana Hotel can improve the implementation of wastewater management aspects for operational purposes, strengthening policies and more structured energy efficiency, and increasing education for staff and guests regarding the importance of sustainability in the hospitality industry.